Patient Experiences With Telemental Health During the COVID-19 Pandemic. (December 2022) - Steidtmann, Dana; McBride, Samantha; Mishkind, Matthew
Telemental health (TMH) was an effective and relatively well-accepted way of delivering mental health care prior to the COVID-19 pandemic and has become widely adopted through the pandemic. Although recent findings show telehealth remains relatively well accepted across health care broadly, little is known about how patient experiences of TMH may have changed through the pandemic as many sectors were virtualized. These findings describe patient experiences with TMH at an outpatient mental health clinic approximately 1 year after the clinic rapidly transitioned to full TMH due to COVID-19. Respondents are 137 adult patients. Most patients reported TMH to be extremely or very effective (85.0%) and better than anticipated (76.8%). Most patients (74.6%) were interested in continuing at least some visits by TMH after the pandemic. A small subset of patients who rated their relationship with their provider as better in-person than by TMH also reported a preference for most or all visits in-person. Results provide preliminary support that TMH remains a well-accepted option for many patients. Mental health clinics may best serve patients by offering a hybrid model of care that includes both TMH and in-person services.